2020
DOI: 10.1002/sdtp.13900
|View full text |Cite
|
Sign up to set email alerts
|

31‐1: Invited Paper: The Multimodal Thin‐Film Transistor (MMT): A Versatile Low‐Power and High‐Gain Device with Inherent Linear Response

Abstract: A new device, the Multimodal Transistor (MMT), separates charge injection from conduction. With design optimization, it can achieve a constant transconductance with independent on/off switching of output current. This functionality has ample applications in energy efficient analog computation and hardware learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…In particular, some studies have demonstrated high- An amplifier device using MMT, which has a similar structure to the split-gate, has been reported. Bestelink et al proposed MMT using two control gates (CG) [87]. CG1 is responsible for regulating the current magnitude, while CG2 performs transportation or blocks the flow of charge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, some studies have demonstrated high- An amplifier device using MMT, which has a similar structure to the split-gate, has been reported. Bestelink et al proposed MMT using two control gates (CG) [87]. CG1 is responsible for regulating the current magnitude, while CG2 performs transportation or blocks the flow of charge.…”
Section: Discussionmentioning
confidence: 99%
“…( f ) Output curve where the value of CG2 is fixed, and it turns on linearly when the voltage is increased by 2 V in CG1. ( g ) Transfer curve and transconductance obtained by applying a fixed voltage to CG2 and sweeping the gate range with CG1 [ 87 ] (adapted from [ 87 ] with permission from The Society for Information Display).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Contact-controlled transistors using multiple gates to independently control charge injection from charge transport are called multimodal transistors (MMTs). They have recently been demonstrated in microcrystalline silicon [1], [2] but the concept can be translated, with ease, to other material systems.…”
Section: Introductionmentioning
confidence: 99%